Neurocognitive, psychosocial and functional status of individuals with alcohol-related brain damage (ARBD) on admission to specialist residential care. (3rd September 2015) - Horton, Lindsay; Duffy, Tim; Martin, Colin
Abstract: Alcohol-related brain damage (ARBD) is a complex neuropsychiatric condition with a multifaceted impact on functioning and the ability to live independently. A comprehensive approach to assessing ARBD is therefore necessary. This study aimed to investigate the neurocognitive, psychosocial and everyday functioning of a group of individuals with ARBD on admission to specialist residential care. A comprehensive assessment framework was used to investigate the baseline functioning of 20 individuals with ARBD. The following assessment tools were administered: the National Adult Reading Test (NART); a selection of Cambridge Neuropsychological Test Automated Battery (CANTAB) tasks; the EuroQoL EQ-5D-5L; the Medical Outcomes Study 36-item Short Form Version 2, acute version (SF-36v2); the Profile of Mood States; the Hospital Anxiety and Depression Scale (HADS); the Depression, Anxiety and Stress Scales (DASS); and the Assessment of Motor and Process Skills (AMPS). The results demonstrate the heterogeneity of individuals with ARBD. There was variability across the group. However, the results indicate a broad pattern of deficits across neurocognitive domains. The majority of participants scored within the normal range for depression, anxiety and stress, although there was evidence for mild to extreme levels of depression and anxiety, as well as elevated levels of confusion and relatively low levels of vigour. Scores on the AMPS also showed variability and most participants demonstrated increased clumsiness and physical effort, and decreased efficiency while performing activities of daily living. Larger scale, longitudinal research is now required to investigate changes in the functioning of people with ARBD over time.